1980
DOI: 10.1136/bjo.64.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Acquired optociliary shunt vessels in papilloedema.

Abstract: SUMMARY Seven cases are presented in which prolonged papilloedema led to the development of acquired optociliary shunt vessels. These vessels may also be found with optic nerve tumours, particularly spheno-orbital meningiomas, optic nerve drusen, glaucoma, and after central retinal vein occlusion. Two A 37-year-old housewife was admitted for increasing weakness of the left arm and leg of 2 years duration and several recent attacks of focal epilepsy. Her past history included migraine episodes for the past 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…There are few reports describing regression of these retinochoroidal venous collaterals including: following decompression of orbito-cranial tumor, 3,15 after optic nerve sheath fenestration, 1,12 post-shunting procedures, 2 and treatment with lumbar puncture and acetazolamide. 13 In our patient, fundus photographs taken just three days postoperatively showed dramatic decrease in caliber of the retinociliary collaterals in both eyes.…”
Section: Discussionmentioning
confidence: 98%
“…There are few reports describing regression of these retinochoroidal venous collaterals including: following decompression of orbito-cranial tumor, 3,15 after optic nerve sheath fenestration, 1,12 post-shunting procedures, 2 and treatment with lumbar puncture and acetazolamide. 13 In our patient, fundus photographs taken just three days postoperatively showed dramatic decrease in caliber of the retinociliary collaterals in both eyes.…”
Section: Discussionmentioning
confidence: 98%
“…A review by Dutton [1] found primary ONSMs to represent 1.3% (22 of 1,723) of all meningiomas with an identifiable site of origin. The presence of optociliary shunts in ONSM, as a chronic sign of the disease, is well known; they represent collateral vessels connecting the choroidal and the retinal vasculature [2]. In our patient, optociliary shunt vessels were not seen because of the moderate edema and the short course of the disease.…”
Section: Discussionmentioning
confidence: 54%
“…[9][10][11] Funduscopic examination of the optic discs should include an assessment of specific features of disc edema including the degree of disc swelling, optic disc color, peripapillary retinal nerve fiber layer opacification, loss of spontaneous venous pulsations, choroidal folds, and hemorrhage or nerve fiber layer infarction around the optic disc. [12][13][14][15] Clinically, papilledema is classified into 4 different stages-early, fully developed, chronic, and atrophic. There are grading scales, including the Frisen scale, that judge the severity of optic disc edema using ophthalmoscopy.…”
Section: Pathogenesismentioning
confidence: 99%